Perioperative pentoxifylline therapy attenuates early postoperative neuro-cognitive decline in patients undergoing coronary artery bypass grafting surgery using cardiopulmonary bypass - Sambhunath Das; Suparna Kailash; Manu Mehta; Akshya Kumar Bisoi (Journal of Neuroanaesthesiology and Critical Care, 2015)
Background: Postoperative cognitive decline (POCD) after coronary artery bypass grafting (CABG) is a common problem. Studies show that pentoxifylline administration reduces inflammation induced by cardiopulmonary bypass and brain injury after ischaemia. Hence the perioperative use of pentoxifylline in attenuating POCD was evaluated in the study. Materials and Methods: Eighty patients were divided randomly into two groups from 106 patients scheduled for CABG surgery. The study group was administered pentoxifylline 400 mg twice daily orally from day of admission to 7th day after surgery, whereas the control group patients received placebo. Neurocognitive assessment was assessed by an independent clinical psychologist one day after admission to hospital and again on 7th postoperative day. The data was analyzed and a P < 0.05 was considered significant results. Results: Pentoxifylline-treated group showed no statistically significant difference in animal naming test scores (10.3 ± 2.2 versus 9.4 ± 2.5, P = 0.07), digit symbol substitution test (26.1 ± 7.47 vs 22.2 ± 6.07, P = 0.09) and 8 subtests of Post Graduate Institute-memory scale. The control group had significant POCD as detected by animal naming test (10.5 ± 3.7 versus 8.6 ± 3.9, P = 0.008), digit symbol substitution test (20.2 ± 8.2 versus 14.7 ± 8.9, P = 0.008) and five subtests of memory scale (P = 0.01, 0.04, 0.003, 0.005 and 0.02). The incidence of POCD was 50% in placebo-treated group compared to 22.5% in pentoxifylline group. Conclusions: The perioperative use of pentoxifylline attenuates the early postoperative neurocognitive decline after CABG using cardiopulmonary bypass.